2017
DOI: 10.1103/physrevb.96.075146
|View full text |Cite
|
Sign up to set email alerts
|

Many-body localization in spin chain systems with quasiperiodic fields

Abstract: We study the many-body localization of spin chain systems with quasiperiodic fields. We identify the lower bound for the critical disorder necessary to drive the transition between the thermal and many-body localized phase to be W cl ∼ 1.85, based on finite-size scaling of entanglement entropy and fluctuations of the bipartite magnetization. We also examine the time evolution of the entanglement entropy of an initial product state where we find power-law and logarithmic growth for the thermal and many-body loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 75 publications
(91 reference statements)
7
56
2
Order By: Relevance
“…In the ETH phase (h ≤ h * ), we observe a sublinear scaling of the natural orbitals, compatible with a survival of the free fermions multifractality. Moreover, we find sub-diffusive dynamics for both imbalance and growth of entanglement entropy, a result which is a bit surprising -but in line with some results on the quasiperiodic Aubry-André model [37,71,83,84] -as the Fibonacci potential is free of rare Griffiths regions, which are usually thought [15,16] to cause such power-law behaviors.…”
Section: Resultssupporting
confidence: 89%
“…In the ETH phase (h ≤ h * ), we observe a sublinear scaling of the natural orbitals, compatible with a survival of the free fermions multifractality. Moreover, we find sub-diffusive dynamics for both imbalance and growth of entanglement entropy, a result which is a bit surprising -but in line with some results on the quasiperiodic Aubry-André model [37,71,83,84] -as the Fibonacci potential is free of rare Griffiths regions, which are usually thought [15,16] to cause such power-law behaviors.…”
Section: Resultssupporting
confidence: 89%
“…Our results can be expected to have relevance for the debate on many-body localization due to disorder versus localization due to pseudo-disorder [15][16][17][18][19]. It was indeed observed that, contrary to naive expectations, adding interactions in quasiperiodic systems does not enhance delocalization, and a MBL transition is observed both in Fibonacci spin chains [19] and in fermionic Aubry-André models [18].…”
Section: Conclusion and Discussionmentioning
confidence: 55%
“…Surprisingly, before the MBL transition there exists a substantial range of λ in which the memory of the initial state relaxes very slowly, although the system is presumbly in a thermal phase [38,39]. Proposed explanations for this slow dynamics include local fluctuations in the initial state and atypical transition rates between single-particle states [38,40,41]. However, our understanding of this regime of slow relaxation in the AA model is still rather incomplete, since it cannot arise from the usual Griffiths physics of rare spatial regions in a deterministic system.…”
mentioning
confidence: 99%